PENDEKATAN INTEGRITAS MODEL PENINGKATAN KINERJA ASN KANTOR KEMENTERIAN AGAMA KABUPATEN NAGAN RAYA (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2019)
This study intended to explore how integrity approach can be promoted as the most effective model in improving the work performance of the civil servants. The study was performed in a descriptive design within the scope of qualitative research. Data was collected through observation, interview, and documentary research. Meanwhile, the procedure for data analysis was performed through reduction, tabulation, and data verification or making a conclusion. Based on all data obtained, it can be summarized that the higher integrity a civil servant embraced in internalizing the attitude of sincerity, honesty, discipline and responsibility when working, the better work performance they can show in doing their duty and functionality.